Floral diversity and taxonomic structure of the florat of he Pivnichne Prychornomoria (Northern Black Sea Coastal Plain) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Spontaneous flora of the northern Black Sea region includes 2025 species and 59 subspecies of vascular plants that belong to 697 genera and 143 families of 5 divisions. In terms of floristic wealth studied flora takes a high position among similar in size floras of Eastern Europe and contains 44,6% of spontaneous vascular plants of Ukraine. High floristic wealth territory study is determined by the multilevel differentiation of the Northern Black Sea and its attendant ecotonic effect. Human economic activity also contributes to the growth of floral wealth in this transformation phase, as the process of biodiversity antropofitamy far ahead of oncoming extinction process of natural flora. The article presents a quantitative characterization of species composition of major taxonomic units, the basic proportions of investigated flora (Liliopsida / Magnoliopsida; genera / species, families / genera / species), species richness of spectra of the leading families and genera, which although in general correspond to the same parameters in the flora of Holarktyky, but is closer to the synanthropic flora. A key indicator of taxonomic structure flora is range of leading families and genera, which reflects the main properties of the flora. The spectrum is dominated by the following families: Asteraceae (257 species; 12,8%), Poaceae (191; 9,5), Fabaceae (127; 6,3), Brassicaceae (124; 6,2), Caryophyllaceae (108; 5,4 ), Rosaceae (87; 4,3), Lamiaceae (76; 3,8), Apiaceae (69; 3,4), Cyperaceae (69; 3,4), Chenopodiaceae (68, 3,4). The most polymorphic genera are Carex (33 species; 1,6%), Euphorbia (24; 1,2), Trifolium (23; 1,1), Centaurea (23; 1,1), Astragalus (23, 1,1), Galium (21; 1,0), Rosa (18; 0,9), Potentilla (18; 0,9), Veronica (17; 0,8), Dianthus (17; 0,8), Artemisia (17; 0,8). The analysis showed a significant transformation of systematic structure as the result of floral synanthropisation, that can be observed in a concentration of a large number of species in a few genera and families; in the growing importance of genera with few species; in shifting of the spectra of leading taxa, including the improving of position in the Brassicaceae and Chenopodiaceae spectrum and Euphorbia, Veronica genera; on the contrary, the growth in the amount of Poaceae and Asteraceae declines as a result of synanthropisation of Caryophyllaceae, Cyperaceae, Lamiaceae i Rosaceae families.
Keywords: Northern Black Sea coastal region, flora of vascular plants, floral diversity, taxonomic structure, synantropisation.